Experimental validation of additively manufactured optimized shapes for passive cooling. (15th September 2018) - Lazarov, Boyan S.; Sigmund, Ole; Meyer, Knud E.; Alexandersen, Joe
Highlights: The superior performance of topology optimized passive heat sinks is demonstrated experimentally. Significant material savings and design improvements of passive LED coolers are confirmed. Easy manufacturable design interpretation demonstrates a methodology for cost reduction. Significant reduction of maintenance costs is estimated based on the measured reduction in the LED temperature. Abstract: This article confirms the superior performance of topology optimized heat sinks compared to lattice designs and suggests simpler manufacturable pin-fin design interpretations. The development is driven by the wide adoption of light-emitting-diode (LED) lamps for industrial and residential lighting. Even for advanced lighting technology as LEDs, a large fraction of the input power is still converted to heat. Thus, efficient thermal control lowers energy waste, increases lifetime and reduces maintenance costs of this rapidly growing, expectedly soon to be governing, illumination technology. The presented heat sink solutions are generated by topology optimization, a computational morphogenesis approach with ultimate design freedom, relying on high-performance computing and simulation. Optimized devices exhibit complex and organic-looking topologies which are realized with the help of additive manufacturing. To reduce manufacturing cost, a simplified interpretation of the optimized design is produced and validated as well. Numerical and experimental results agree well and indicate that the obtained designs outperform lattice geometries by more than 21%, resulting in a doubling of life expectancy and 50% decrease in operational cost.